2011
DOI: 10.1109/tuffc.2011.1900
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the spatial resolution of different high-frequency imaging systems using a novel anechoic-sphere phantom

Abstract: The spatial resolution of high-frequency ultrasound (HFU, >20 MHz) imaging systems is usually determined using wires perpendicular to the beam. Recently, two tissue-mimicking phantoms (TMPs) were developed to estimate the three-dimensional (3D) resolution. Each of the TMPs consist of nine, 1 cm wide slabs of tissue-mimicking material containing randomly distributed anechoic spheres. All anechoic spheres in one slab have the same dimensions, and their diameter is increased from 0.1 mm in the first slab to 1.09 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…2(c5)]. This showed that despite the better contrast and SNR provided by the linear array, the annular array had a higher effective resolution and enabled a better detection of the pipes smaller than 200 μ m. A similar result was found in a previous study [6] using phantoms with anechoic spheres 200 μ m in diameter.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…2(c5)]. This showed that despite the better contrast and SNR provided by the linear array, the annular array had a higher effective resolution and enabled a better detection of the pipes smaller than 200 μ m. A similar result was found in a previous study [6] using phantoms with anechoic spheres 200 μ m in diameter.…”
Section: Resultssupporting
confidence: 82%
“…Tissue-mimicking (TM) phantoms can be used to provide a more realistic medium for device characterization because they simulate conditions more relevant to scanning within tissue. In a previous study [6], we characterized the detection capabilities of a custom HF imaging system based on an annular-array transducer, and two HF commercial scanners from VisualSonics (VisualSonics Inc., Toronto, ON, Canada): the Vevo 770 (single-element transducer) and Vevo 2100 (linear-array transducer). The characterization method was based on a TM phantom containing anechoic spheres with sizes ranging from 1090 to 100 μ m. The ability of the scanners to detect those spheres was dependent on their spatial resolution in all directions simultaneously (3D resolution).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we used a 40 MHz, 5-element annular array, and a synthetic-focusing (SF) algorithm to achieve a sixfold increase in DOF compared to an equivalent single-element transducer. 7,8 Using a similar array, we demonstrated combined high-frequency (HF) ultrasound (HFU) and PAI with broad, uniform illumination from a bifurcated optical-fiber assembly. 9 One application that is gaining attention is vascular imaging in small animals, such as mice, for studying human disease 10,11 and mammalian development.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the anechoic spheres was in the range of 280 to 350 μm, controlled by two dedicated sieves (Fisherbrand sieves, Fisher Scientific, Pittsburgh, PA). The contrast-to-noise ratio (CNR) of the anechoic spheres against the background, which was described in detail by Filoux et al [38], was used to evaluate the improvement of depth-of-field by the proposed imaging platform.…”
Section: F Test Schemementioning
confidence: 99%